Prevalence of Obesity among Affluent School Children in Dhaka - Mohsin, F; Tayyeb, S; Baki, A; Sarker, S; Zabeen, B; Begum, T; Azad, K; Nahar, N (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):549-54 The abstract of this article is available on the PubMed website